Analyses of human immune responses to Francisella tularensis identify correlates of protection - Lindgren, Helena; Eneslätt, Kjell; Golovliov, Igor; Gelhaus, Carl; Sjöstedt, Anders (Frontiers in Immunology, 2023)
Francisella tularensis is a highly contagious bacterium and the etiological agent of the potentially severe infection tularemia. An existing F: tularensis vaccine, the live vaccine strain, has been used to protect at-risk personnel, but it is not licensed in any country. Detailed analysis of the characteristics of the immune response to F. tularensis will generate crucial knowledge regarding new vaccine candidates. In order to identify such correlates of protection and immunity, the properties of peripheral blood monocytes (PBMC) collected from nine donors before and after vaccination were studied. Unlike PBMC collected before vaccination, PBMC collected at four time points up to one year after vaccination demonstrated F. tularensis-specific cell proliferation, cytokine secretion and cytokine-expressing memory cells. In response to F. tularensis antigen, a majority of 17 cytokines were secreted at higher levels by PBMC collected at all four time points after vaccination than before vaccination. A discriminative analysis based on IFN-γ and IL-13 secretion correctly classified samples obtained before and after vaccination. Intracellular cytokine staining identified the most significant changes among the CD4 transient memory, CD8 effector memory, and CD8 transient memory T-cell populations and increased expression of IFN-γ, IL-2, and MIP-1β were observed at all time points after vaccination vs. before vaccination. Growth restriction of the highly virulent F. tularensis strain SCHU S4 in monocyte-derived macrophage cultures was conferred by supernatants from F. tularensisstimulated PBMC cultures and protection correlated to levels of IFN-γ, IL-2, TNF, and IL-17. The findings demonstrate that F. tularensis vaccination induces long-term T-cell reactivity including T EM and T TM cell populations. Individual cytokine levels correlated with the degree of protection conferred by the supernatants. Identification of such memory T cells and effector mechanisms provide an improved understanding of the protective mechanisms against F. tularensis.